Analysis of Factors Affecting Motor Vehicle Taxpayer Compliance at UPT PPD Samsat Pandan, Tapanuli Central Regency - Lubis, Ardiansyah Putra; Erlina, Erlina; Tarmizi, Tarmizi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The objectives of this study are to 1) Analyze the effect of taxpayer awareness on motor vehicle taxpayer compliance at UPT PPD Samsat Pandan, Central Tapanuli Regency, 2) Analyze the effect of the imposition of administrative sanctions on motor vehicle taxpayer compliance at UPT PPD Samsat Pandan, Central Tapanuli Regency, 3) Analyzing the effect of imposition of fines on the compliance of motorized vehicle taxpayers at UPT PPD Samsat Pandan, Central Tapanuli Regency, 4) Analyzing the effect of joint taxpayer awareness, imposition of administrative sanctions, and imposition of fines on compliance with motor vehicle taxpayers at UPT PPD Samsat Pandan, Central Tapanuli Regency, and 5) Analyzing the relationship between motor vehicle taxpayer compliance in the development of the Central Tapanuli Regency area. The research was conducted in Central Tapanuli Regency on the Analysis of Factors Affecting Motor Vehicle Taxpayer Compliance at UPT PPD Samsat Pandan, Central Tapanuli Regency. The analytical method used in this research is multiple regression analysis. The results showed that taxpayer awareness had a positive and significant effect on motor vehicle taxpayer compliance at UPT PPD Samsat Pandan, Central Tapanuli Regency. The imposition of administrative sanctions has a positive and significant effect on the compliance of motor vehicle taxpayers at UPT PPD Samsat Pandan, Central Tapanuli Regency. The imposition of fines has a positive and significant impact on motor vehicle taxpayer compliance at the UPT PPD Samsat Pandan, Central Tapanuli Regency. The awareness of taxpayers, the imposition of administrative sanctions and the imposition of fines together have a positive and significant effect on the compliance of motor vehicle taxpayers at UPT PPD Samsat Pandan, Central Tapanuli Regency. Motor vehicle tax compliance is related to the development of the Central Tapanuli Regency area.